An Opportunity And Policy to Improve Performance of Peanut Agribusiness in South Sulawesi - Bambang Sayaka; Muhammad Maulana; Deri Hidayat (Analisis Kebijakan Pertanian, 2011)
Peanut agribusiness in South Sulawesi does not develop optimally. During harvest season the peanut production of this province is sufficient to meet local demand and is sold for inter-island trade. During off-season local demand for peanut is fulfilled through inter-island trade and import. The traders usually buy fresh pods and dried pods from the farmers and traders’ profits are earned through processing them into dried beans. Retailers in urban areas sell fresh pods and dried beans. The main consumers of dried beans are local peanut processors. Credit access for the farmers may improve quantity and quality of peanut production. Roads improvement in peanut producing centers may accelerate peanut transportation and reduce its transportation cost. Illegal retribution should be removed. The traders need credit access for their business scale improvement. Partnership between the farmers and the peanut processing companies will enhance peanut agribusiness in South Sulawesi Province.